Plasma arginine vasopressin concentrations and antidiuretic action of carbamazepine. Issue 6125 (3rd June 1978) - Stephens, W P; Coe, J Y; Baylis, P H
Abstract : Twelve subjects given therapeutic doses of carbamazepine showed no change in their plasma electrolyte concentrations. Ten of the 12 had abnormal water metabolism, however, their ability to excrete water loads being decreased. Plasma arginine vasopressin (AVP) concentrations fell while the subjects were taking the drug, indicating that the mechanism is unlikely to be increased secretion of antidiuretic hormone. We suggest that the water-retaining property of carbamazepine is a physiological effect of the drug, mediated by increased renal sensitivity to normal plasma concentrations of AVP and resetting of osmoreceptors.